O ensino de violino no curso básico da Escola de Música da UFRN: reflexões sobre a prática - Petrolino, Maria Isabel Brasiliano (2010)
This paper aims to report an internship teaching experience conducted in the Elementary Violin Course at the Federal University of Rio Grande do Norte Music School. The research process project was conducted over three semesters, and was applied to various trials of teaching training in the classroom. The reference methodologies were those of Shinichi Suzuki, Suzan Kempter, Ivan Galamian, Demetrius Constantine Dounis, Simon Fischer, Linda Kruger, Maia Bang and Barbara Barber, as well as the current research on the methodology of teaching the violin. Analyses of the experimental teaching trials were performed, compared with the present Violin Elementary Course Curriculum, including pedagogical guidelines. Modifications in the curriculum and pedagogical guidelines are suggestions in light of the results obtained.